Sexual dysfunctions in patients with diabetes: a study from Iran - Montazeri Ali; Vahdaninia Mariam; Ziaei-Rad Marzieh (BMC, 2010)
Abstract Background Diabetes mellitus is a chronic disease that causes short and long-term complications. This study aimed to investigate the prevalence of sexual dysfunctions (SD) among diabetic patients in Iran and to examine whether glycemic control has a role in SD. Methods A consecutive sample of diabetic women and men who were registered in the Isfahan Endocrine and Metabolism Center, Iran were studied. Sexual dysfunction was evaluated using the Female Sexual Function Index (FSFI) in women and the International Index of Erectile Function (IIEF) in men. In addition the level of glycosylated hemoglobin was assessed to classify the diabetes status in patients. Results In all 200 patients (100 male and 100 female) were entered into the study. The mean age of patients was 48.6 (SD = 7.3) years and most had type 2 diabetes (91.0%). The results showed that sexual dysfunctions were widespread in both gender and 165 (82.5%) patients reported that experienced at least one sexual dysfunction. There were significant associations between sexual dysfunctions and gender and type of diabetes (P = 0.04). Women and patients with type 1 diabetes had higher rates of SD. No major differences were found between SD and age, diabetes status, duration of diabetes and hypertension. In addition, glycemic control did not show a significant association with SD in both genders. Conclusion The findings of this study showed that SD prevalence was high in diabetic patients of both genders and the glycemic control did not correlate with the frequency of SD in the study population. It is recommended that SD should be addressed more precisely in health care practice in Iran.